C.2 - Pillai, P.S.A. (Gurgaon, 2013)
Written in a simple and lucid style and supported with richauthorities, judicial as well as scholarly, this latest editionwill retain its decades old appeal for all persons interested inthe field of criminal law. This book is an essential companion forpractitioners, academicians and trial court judges, especiallythose at the outset of their careers. The Current edition will be awelcome entrant to the libraries of senior members of theprofession, many of whom have relied, at one time or another, onthe book as a handy reference. It will also be indispensablereading for students of law pursuing their LLB, LLM, and DoctoralDegrees in the field of Criminal Law
Keywords: Criminal law-India cases